(3GdeQLY GdSQjY ai (B\cs - (3LdGd NQSI (B.s; (3QGei YGUi , eYO(B.s ((3ShQjI (B:s (3TYGY ddfTQ h GdYdhe(B,s, 2005)
(3jYJHQ gPG GdcJGH eQLYG SQjY ai dZI GdHQeLI h GWGQ GdYed (Bnet.s
(3jJfGhd GdcJGH dZI GdHQeLI(B.s
All age.
Keywords: (3dZI GdHQeLI(B.s